The Influence of Melatonin Treatment in the Vinification of Feteasca Neagra and Cabernet Sauvignon Wines on the Profile of Polyphenolic Compounds and Antioxidant Activity - Sandra A. V. Eremia; Camelia Albu; Gabriel-Lucian Radu; Andreia Alecu; Elena Brinduse (MDPI AG, 2023)
Until recently, the main antioxidant role among wine constituents was attributed to polyphenolic compounds, but once the presence of melatonin in wines was confirmed, an interesting new field of research opened up due to its possible synergistic effects with other antioxidants in the winemaking process, which may lead to a change in the profile of polyphenolic compounds and antioxidant activity. In order to investigate the evolution of active principles from the phenylpropanoid metabolism associated with the synergistic effects of melatonin, for the first time, a melatonin treatment was performed in the pre-stage of the different winemaking processes of Feteasca Neagra and Cabernet Sauvignon wines with different melatonin concentrations. After comparing the acquired results for the evolution of the polyphenolic compound profile and antioxidant activity of treated wines, we ascertained an increase in the antioxidant compound concentrations, especially in resveratrol, quercetin, and cyanidin-3-glucoside, directly proportional to the used melatonin concentration; an intensification in activity of PAL and C4H enzymes; and the modification in the expression of specific anthocyanin biosynthesis genes, especially UDP-D-glucose-flavonoid-3-O-glycosyltransferase. It was also shown that the application of melatonin in the pre-stage of the winemaking process can be successfully used to obtain red wines with increased antioxidant activity (almost 14%).